Economic and Ecological Benefit Evaluation of Clean Energy Power Generation Projects in Minority Areas—Taking F Project as an Example - Wen, Huixin (Journal of Global Economy, Business and Finance, 2025)
Clarifying the actual benefits of the project is an important reference for government departments to promote the transformation of the clean industry in ethnic minority areas. Focusing on the clean energy characteristics in ethnic regions and the advantages and disadvantages of clean energy projects, this paper constructs a benefit evaluation system for multi-energy complementary projects from the perspectives of ecology and economics based on externality theory, systems theory, ethnic economic development theory and sustainable development theory. It also uses value substitution method, ecological value accounting method, remote sensing inversion method and cost-benefit analysis method for comprehensive measurement and analysis. Taking the Qinghai F project with prominent ethnic characteristics and relatively mature multi-energy complementary projects as a case study, this paper uses field survey data, data in the project feasibility report and remote sensing satellite data to evaluate its ecological benefits, economic benefits and spillover benefits, and deeply explores the actual value of the multi-energy complementary projects of clean energy power generation in ethnic areas. The main research conclusions are as follows: (1) The carbon emission reduction of the F project in 25 years is 37.9625 million tons, the emission reduction value is 2.24 billion yuan, and the carbon fixation and oxygen release value of the project is 77,282.39 yuan, which highlights the core contribution of the multi-energy complementary project to the “dual carbon” goal. Clean energy development in ethnic minority areas can effectively reduce greenhouse gas emissions and has good ecological benefits. (2) Based on the vegetation coverage in different operation periods of the project inverted based on remote sensing data, the trend of vegetation coverage in the study area was analyzed. It can be seen that the area of desertified land has decreased significantly, and the area of photovoltaic-grassland system has increased. This proves the potential of the “photovoltaic + ecology” model for desertification land governance and achieves synergistic efficiency between ecological restoration and renewable energy development. (3) Over the 25 years, the total cost of Project F was RMB 1.473 billion, the total revenue was RMB 2.188 billion, and the return on investment was 48.49%. The economic benefits are considerable, but there is a problem of over-reliance on government subsidies. (4) The ecological cost of Project F accounts for 1.03% of the total cost, but the benefits and value spillover account for 12.06% and 34.79% of the total value, respectively. The asymmetric relationship between ecological costs and benefits was revealed, and it was demonstrated that the multi-energy complementary system in ethnic areas has the characteristics of ecological input-output nonlinear gain. This shows that the project has great potential in terms of ecological benefits, but it has not yet been fully released.